2006
DOI: 10.1007/bf02664942
|View full text |Cite
|
Sign up to set email alerts
|

Giant splenic metastasis due to lung adenocarcinoma

Abstract: Lung cancer is the most prevalent malignancy in western countries and most of the patients present at advanced stages, but single splenic metastasis is exceptional instead. We report on a case of a seventy- three-year old male presenting with non-hemoptoic productive cough, constitutional syndrome and pain in the left lower quadrant. Physical examination and complementary radiological and histological procedures revealed the presence of an adenocarcinoma of the left lung with probable splenic metastasis. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
1
8
0
1
Order By: Relevance
“…This finding is supported by several recently reported cases [3,4,12,13]. However in our patient, the primary lung cancer was in the right lung.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is supported by several recently reported cases [3,4,12,13]. However in our patient, the primary lung cancer was in the right lung.…”
Section: Discussionsupporting
confidence: 92%
“…This is probably due to its high density of immune-system cells, its role in ''immune surveillance'' and its high concentration of angiogenesis inhibition factor [3,4]. However, isolated splenic metastasis is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was concluded at that time that spleen mass accompanying metastasis to other abdominal organs in patients with a known lung cancer should be regarded as a metastasis. We recently conducted a review of patients with lung cancer and spleen metastasis, and found 20 such patients (10)(11)(12)(13)(14)(15)17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). In these 20 patients, it was notable that all but 4 of the 20 patients had no abdominal metastasis other than spleen metastasis.…”
Section: A B Cmentioning
confidence: 99%
“…6 Dalak arterin keskin bir açile dallanması, dalağın doğal ritmik kontraktil yapısı, afferent lenfatik yolağın olmaması, anjiyogenezi inhibe eden faktörlerin yüksek konsantrasyonu ve yoğun lenfoid doku nedeni ile tümör embolilerin solid dokuya ulaşmasının zorlaşması gibi birtakım mekanizmalar ile metastaza karşı direnç açıklan-maya çalışılmıştır. 7,8 Literatürde çoğunlukla bulunan olgu sunumları dışında yapılan klinik patolojik çalışmalar (cerrahi veya otopsi serileri) ile metastaza karşı direnç açıklanmaya çalışılmıştır. Yaygın hastalığa sahip olanlarda, splenik rüptür ya da hipersplenizm dışında tedavi yaklaşımı primer tümö-rün tedavisi şeklinde olmaktadır.…”
Section: E Funclassified